Dehydration triggers ecdysone-mediated recognition-protein priming and elevated anti-bacterial immune responses in Drosophila Malpighian tubule renal cells - Wenjing Zheng (BMC Biology, 2018)
Abstract Background Drosophila is a powerful model for the study of factors modulating innate immunity. This study examines the effect of water-loss dehydration on innate immune responsiveness in the Drosophila renal system (Malpighian tubules; MTs), and how this leads to elevated host defense and contributes to immunosenescence. Results A short period of desiccation-elevated peptidoglycan recognition protein-LC (PGRP-LC) expression in MTs, increased antimicrobial peptide (AMP) gene induction, and protected animals from bacterial infection. We show that desiccation increased ecdysone synthesis in MTs, while inhibition of ecdysone synthesis or ecdysone receptor expression, specifically within MTs, prevented induction of PGRP-LC and reduced protection from bacterial infection. Additionally, aged flies are constitutively water-stressed and have elevated levels of ecdysone and PGRP-LC. Conversely, adults aged at high relative humidity show less water loss and have reduced expression of PGRP-LC and AMPs. Conclusions The Drosophila renal system is an important contributor to host defense and can modulate immune responses in an organ autonomous manner, responding to environmental changes such as desiccation. Desiccation primes immune responsiveness by elevating PGRP-LC expression specifically in MTs. In response to desiccation, ecdysone is produced in MTs and acts in a paracrine fashion to increase PGRP-LC expression, immune responsiveness, and improve host defense. This activity of the renal system may contribute to the immunosenescence observed in Drosophila.